2015
DOI: 10.1534/g3.114.015040
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Ethanol Exposure Leads to Dysregulation of Lipid Metabolism and Oxidative Stress in Drosophila

Abstract: Ethanol exposure during development causes an array of developmental abnormalities, both physiological and behavioral. In mammals, these abnormalities are collectively known as fetal alcohol effects (FAE) or fetal alcohol spectrum disorder (FASD). We have established a Drosophila melanogaster model of FASD and have previously shown that developmental ethanol exposure in flies leads to reduced expression of insulin-like peptides (dILPs) and their receptor. In this work, we link that observation to dysregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…Therefore, the upregulation of uro under MD conditions might not be directly linked to dietary urea. uro is involved in many stress-related pathways, such as exposure to ethanol (Logan-Garbisch et al, 2014) or oxidative stress (Terhzaz et al, 2010). Other studies have also reported an upregulation of uro in cold-exposed Drosophila adults (Zhang et al, 2011;Boardman et al, 2017); therefore, this gene probably has multiple functions related to stress-tolerance mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the upregulation of uro under MD conditions might not be directly linked to dietary urea. uro is involved in many stress-related pathways, such as exposure to ethanol (Logan-Garbisch et al, 2014) or oxidative stress (Terhzaz et al, 2010). Other studies have also reported an upregulation of uro in cold-exposed Drosophila adults (Zhang et al, 2011;Boardman et al, 2017); therefore, this gene probably has multiple functions related to stress-tolerance mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…| 885 localized within glial cells. In contrast, it has been described that accumulation of excess fatty acids in cellular triacylglyceride stores may be protective against lipotoxicity (Listenberger et al, 2003;Logan-Garbisch et al, 2014). Moreover, from our analysis, it seems that triacylglycerides accumulated into LDs are unsaturated lipids due to their high affinity for osmium tetroxide (De Martino, Natali, Bruni, & Accinni, 1968;Digel, Ehehalt, & F€ ullekrug, 2010;Fujimoto et al, 2013).…”
Section: Discussionmentioning
confidence: 50%
“…In normal conditions, the primary function of LDs is to store triacylglycerols and sterol derivatives, which can be mobilized to fuel ß-oxidation for energy generation and to provide membrane precursors (Goodman, 2009;Guo, Cordes, Farese, & Walther, 2009). In contrast, it has been described that accumulation of excess fatty acids in cellular triacylglyceride stores may be protective against lipotoxicity (Listenberger et al, 2003;Logan-Garbisch et al, 2014). Increased number of LDs has been shown in experimental models of cellular stress such as nutrient deprivation (Cabodevilla et al, 2013) and in metabolic or mitochondrial diseases (Greenberg et al, 2011;Bayat et al, 2012;Golla, Ren, Malloy, & Pascual, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We explored the glutathione synthetase region (containing Gss1 and Gss2), which is just one example among hundreds in modENCODE that likely suffer from misleading annotations. A tandem duplication present in ISO1 has created two copies of Gss1 and Gss2, which are associated with toxin metabolism and linked to tolerance to arsenic (Ortiz et al 2009) and ethanol induced oxidative stress (Logan-Garbisch et al 2015). While this duplication segregates at high frequency in DSPR strains (9/13), it is absent in Oregon-R ( Fig.…”
Section: Functional Structural Variation At Mapped Qtlmentioning
confidence: 99%